Dampak Motivasi Investasi, Literasi Keuangan, dan Lingkungan Keluarga Terhadap Minat Investasi Anak Milenial - Addo Ryandana; Sri Hermuningsih; Pristin Prima Sari (Ekonomis: Journal of Economics and Business, 2023)
This study aims to determine the effect of investment motivation, financial literacy, and family environment on millennial children's investment interest. The research method uses quantitative. The population in this study were millennial children aged 20-40 years. The sample used in this study were 100 employees. The sampling technique is based on 25 times the number of variables used, namely 3 independent variables and 1 dependent variable. The tests used in this research are validity, reliability, normality, heteroscedasticity, multicollinearity, multiple linear regression analysis, partial test, simultaneous test, and coefficient of determination test. The results showed that the investment motivation variable partially had a positive and significant effect on millennial children's investment interest, but the financial literacy and family environment variables partially had no significant effect on investment interest. Simultaneously, the variables of investment motivation, financial literacy, and family environment have a positive and significant effect on millennial children's investment interest